A new heart: portraying the physiologic anatomo-functional reconstruction in ischemic cardiomyopathy - Cirillo, Marco; Campana, Marco; Bressanelli, Anna; Troise, Giovanni (Journal of Cardiology and Cardiovascular Medicine, 2017)
Fiber-based model of the left ventricle is known since 1628 but the complex 3D structure of myocardial fibers has not taken into account in normalcy or in disease until the last decade. We here present the case of a 60-year-old female patient affected by ischemic cardiomyopathy and severe left ventricular dysfunction. Left ventricle was reconstructed according to a novel surgical technique aimed at rebuilding an elliptical ventricular chamber and redirecting myocardial bundles of fibers in a near-normal orientation, by means of an original suturing technique. Left ventricular torsion was restored, proving the reorientation of myocardial fibres’ bundles. The restored physiologic shape was maintained along the years, gradually improving global ejection fraction and diastolic indices, showing a positive remodeling induced by the optimised geometrical and functional parameters. The unexpected and never proven before renewal of ventricular torsion is an adjunctive element of ventricular efficiency, mainly in ventricles that work at a critical mechanics. A new fiber-based reading of heart function could improve clinical and functional outcomes and address some unsolved issues in the surgical treatment of ischemic cardiomyopathy as well as in medical approaches to the diseased myocardium.